Glycosides isolated from the aerial parts of Premna integrifolia growing in Thai Binh - Hien, Truong Thi Thu; Tuyet Mai, Ngo Thi; Tam, Bach Thi; Hien, Nguyen Thi Thu; Cuong, Le Canh Viet; Tuan Anh, Hoang Le (Vietnam Journal of Science and Technology, 2019)
From the aerial parts of Premna integrifolia L., three glycosides acteoside (1), premnaodoroside A (2), and premnaodoroside B (3) were isolated. Their chemical structures were elucidated by means of ESI-MS, 1H-NMR, 13C-NMR, HSQC, HMBC spectra and in comparison with the previous literature. To our best knowledge, this is the first report of 1 and 3 from P. integrifolia.